IDENTIFICATION AND IN SILICO ANALYSIS OF INHIBITOR ON THE WNT/β-CATENIN SIGNALING PATHWAY AS POTENTIAL DRUG FOR COLON CANCER - RIDWAN, SALBIAH; ERLINA, LINDA; BAHTIAR, ANTON; SUKMAWATI, DEWI (International Journal of Applied Pharmaceutics, 2023)
Objective: We aimed to predict the PPI network and in silico analysis of a drug that can potentially inhibit colon cancer, specifically in the Wnt/β-catenin signaling pathway, based on pharmacophore modeling and molecular docking. Methods: Target genes involved in colon development were screened for specific genes in the Wnt/b-catenin signaling pathway. Tissue construction and possible signaling pathways were analyzed using protein-protein interactions. Genes with significant centrality and best-grade values ​​were made to feature pharmacophore models and their suitability for potential drugs. Validation was carried out using the molecular docking method for interaction with the best Hits. Results: Protein-Protein Interaction Network (PPI) revealed BTNNB1, TP53, AXIN, FZD-8, and CDK1 as potential critical targets in the Wnt/β-catenin signaling pathway and from the suitability of pharmacophore features obtained 27 drugs as the best Hit compounds. The therapeutic effects of the drugs we found were shown to be related to the synergistic activity (multitarget and multi-path). GO enrichment analysis revealed 36 GO entries, including 11 biological processes, 10 cellular components, and 15 molecular functions. Molecular docking experiments confirmed the correlation between three drugs (Clofazimine, Closantel, and Sulindac) with the best binding to 4 target proteins (AXIN1, TP53, CDK1, and FZD-8). Conclusion: In this study, we found a potent drug that can inhibit colon cancer disease in the Wnt/β-catenin signaling pathway and an essential target protein responsible for the efficacy of colon cancer treatment, providing a theoretical basis for further research.